ON THE BORDER OF THE UKRAINIAN AND POLISH CULTURES – ROSTYSŁAW RADYSZEWSKI - Romaszczenko, Ludmiła (Prace Polonistyczne, 2022)
Rostysław Radyszewski is well-known both in Poland and Ukraine. He is a doctor of philology, professor, a correspondent member of the Ukrainian National Academy of Sciences, a member of the Polish Academy of Learning, and the head of the Department of Polish Studies at the Faculty of Philology of the Kiev National University. The article presents his most important works and monographs and mostly focuses Radyszewski’s contribution to Polish studies and his work that aimed to foster Polish-Ukrainian relations.